Christianity and Islam - the development of modern science nad the genesis of the modern (just) state - D. F. M. Strauss (Acta Theologica)
This article focuses on the formal similarities between Christianity and the Islam resent during the later middle ages — a period in which both legacies subscribed to a relatively totalitarian societal condition manifested in the existence of their respective empires. The ideal of the Corpus Christi as the societas perfecta of medieval Christianity is explained in the light of the contest between church and state during the later middle ages. This legacy was eventually challenged by an intellectual movement initiated by John the Scott and William of Ockham that caused the breaking apart of the former ecclesiastically unified culture. The alternative development within the Islam world is sketched before the spirit of modernity is explained as a secularization of biblical Christianity.  Humanism initially inspired explicitly totalitarian theories of the state. It was only within the Protestant countries of Europe that the modern constitutional state under the rule of law emerged,  accompanied by a process of societal differentiation unparalleled in world history. Although the more recent attempts of Islamic countries to benefit from the fruits of the modern natural sciences  inspired them to introduce the teaching of the natural sciences within the Muslim world, these countries did not succeed in benefiting from the significant transformation of the medieval empires  into modern democratic states. Since the Muslim world is still embedded in the relatively undifferentiated embrace of a societal setting guided and integrated by the Muslim faith it did not succeed  as yet to transcend the inherent limitations entailed in a typical empire in the classical sense of the word.